2010 International Conference on Communications, Circuits and Systems (ICCCAS) 2010
DOI: 10.1109/icccas.2010.5581867
|View full text |Cite
|
Sign up to set email alerts
|

Memristor system properties and its design applications to circuits such as nonvolatile memristor memories

Abstract: Novel nonvolatile universal memory technology is essential for providing required storage for nano-computing. As a potential contender for the next-generation memory, the recently found "the missing fourth circuit element", memristor, has drawn a great deal of research interests. In this paper, by starting from basic memristor device equations that assumes constant ion mobility, we develop a comprehensive set of properties and design equations for memristor based memories. Our analyses are specifically targeti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, memristive-based circuits can be simulated using memristor SPICE models based on experimentally reported TiO 2 memristor results [2]. The memristive range can be modified by scaling from the experimental results [4] and the memristor capacitance can be determined, to first order, from the device geometry and material properties [4][5][6]. This allows the fundamental performance of memristor-based circuits to be explored in anticipation of wider spread device availability and application specific memristor technology development.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…However, memristive-based circuits can be simulated using memristor SPICE models based on experimentally reported TiO 2 memristor results [2]. The memristive range can be modified by scaling from the experimental results [4] and the memristor capacitance can be determined, to first order, from the device geometry and material properties [4][5][6]. This allows the fundamental performance of memristor-based circuits to be explored in anticipation of wider spread device availability and application specific memristor technology development.…”
Section: Introductionmentioning
confidence: 98%
“…This work went largely unnoticed until 2008 when Strukov, et.al., of Hewlett Packard (HP) published the first model description and experimental results of a physical TiO 2 nanoscale memristive device [2] using processes compatible with modern semiconductor fabrication technology [3]. Since this physical development, memristors have been of wide interest due to their unique behavior of resistance memory (memristance) [1,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this approach severely impacts the density advantage of memristor arrays. [10] [11] have shown that the reading phase can be made tolerant to data corruption by applying a sequence of two opposite voltage values; however, as described in [6] the write method has additional issues due to its intrinsically asymmetric nature. this aspect will be analyzed in this manuscript.…”
Section: Introductionmentioning
confidence: 99%
“…Since the first reported use of the memristor, it received a significant of attention in the research community. In addition to be used as a memory element [2,[17][18][19][20][21][22][23][24][25][26], the memristor has found many applications in oscillators [27][28][29][30], logic and arithmetic circuits [31,32], programmable analog circuits [33,34], and in modeling and emulation of natural phenomena [35,36].…”
Section: Introductionmentioning
confidence: 99%